Finite element least-squares methods for a compressible stokes system - Keehwan Kim; Sangdong Kim; Sangsik Shin (International Journal of Mathematics and Mathematical Sciences)
The least-squares functional related to a vorticity variable or a velocity flux variable is considered for two-dimensional compressible Stokes equations. We show ellipticity and continuity in an appropriate product norm for each functional.